Targeting interleukin-13 receptor α2 (IL-13Rα2) for glioblastoma therapy with surface functionalized nanocarriers - Ruijia Liang; Cheng Wu; Shiming Liu; Wenyan Zhao (Taylor & Francis Group, 2022)
Despite surgical and therapeutic advances, glioblastoma multiforme (GBM) is among the most fatal primary brain tumor that is aggressive in nature. Patients with GBM have a median lifespan of just 15 months when treated with the current standard of therapy, which includes surgical resection and concomitant chemo-radiotherapy. In recent years, nanotechnology has shown considerable promise in treating a variety of illnesses, and certain nanomaterials have been proven to pass the blood-brain barrier (BBB) and stay in glioblastoma tissues. Recent preclinical research suggests that the diagnosis and treatment of brain tumor is significantly explored through the intervention of nanomaterials that has showed enhanced effect. In order to elicit an antitumor response, it is necessary to retain the therapeutic candidates within glioblastoma tissues and this job is effectively carried out by nanocarrier particularly functionalized nanocarriers. In the arena of neoplastic diseases including GBM have achieved great attention in recent decades. Furthermore, interleukin-13 receptor α chain variant 2 (IL13Rα2) is a highly expressed and studied target in GBM that is lacked by the surrounding environment. The absence of IL13Rα2 in surrounding normal tissues has made it a suitable target in glioblastoma therapy. In this review article, we highlighted the role of IL13Rα2 as a potential target in GBM along with design and fabrication of efficient targeting strategies for IL13Rα2 through surface functionalized nanocarriers.